Village fund program in Cibeureum and Sukapura village, Bandung Regency, Indonesia: Problems, risks, and solutions - Arwanto Harimas Ginting; Ida Widianingsih; Rahman Mulyawan; Heru Nurasa (Cogent Social Sciences)
The increase in village revenue and expenditure budgets (APBDes) has resulted in many abuses of APBDes in Indonesia. This article seeks to uncover the fundamental problems that lead to misuse of APBDes, namely the process of APBDes preparation, the structure of APBDes, and the primary power holders in the implementation of APBDes, where the Village Fund is the main component in the APBDes structure. By using a qualitative approach and collecting data through interviews and documentation and analyzing it with data reduction, data presentation, and data verification techniques. The research findings explain that it is important to increase direct community participation in the planning and budgeting of village funds, increase the capacity of village officials as a solution to overcome these risks, and strengthen the sub-district government in assisting the management of village funds.